Texts, structures and experiences The society of state socialist Hungary in a historical perspective - Majtényi, György (Socio.hu Társadalomtudományi Szemle, 2014)
In the state socialist system sociology could establish its reason for existence and construct its identity by merely emphasizing the objectivity of its scientific investigations (since to the „real” processes even the power had to pay attention). In this role–interpretation – that can be called ‘socialist modernity’ – the missionary zeal of science, its faith in development, scientific objectivity and in the cognizability of social reality concealed the inevitable, indirect effort of the ideology of power. The discipline has built up it myths in accordance with that concealment. The conclusions of historical studies on state socialism – seemingly well grounded and referenced – are often not only based on the phenomena examined but are also coloured by the period’s accepted conceptual framework. Our present knowledge about the society of the era is, to a large extent, based on these concepts, too. It is this lack of conceptual self–reflection with regard to historiography that explains why several historians believe they are discussing social reality, but are in actual fact only interpreting categories formulated in the wake of various party decrees. Unless we are able to uncover the effects of the identity policy that worked to create the virtual reality of state socialist society, unless we recognize the nature and operation of the various discourses of power and science, we cannot reach a reliable understanding of the period’s phenomena. Key words social history, historiography, conceptual history, stratification, structuration, mobility, modernization, acculturation, everyday life, revisionist historiography, Alltagsgeschichte, Eigensinn, autonomy